The Other Side of Ramadan: Ramadan and its implication on Social Cohesion in West Sumatra and Yogyakarta - Shalihin, Nurus; Yulia, Yulia; Sholihin, Muhammad (Analisa: Journal of Social Science and Religion, 2021)
This article examines the implications of Ramadan on social cohesion in communities in West Sumatra and Yogyakarta. The issue is based on the assumption that Ramadan is a religious momentum that is only concerned with the vertical affairs between humans and their Lord alone and has a social dimension, i.e., values of solidarity, sense of belonging, tolerance, and social harmony. These are fostered through religious rituals such as fasting, zakat, and other kinds of worship. The study adopted a qualitative approach and was supported by survey data on several selected community samples. Survey data was collected related to the volume of philanthropy, the frequency of ritual worship during the month of Ramadan concerning the level of quality of social cohesion, solidarity, and social trustworthiness. In addition, the data were collected through a questionnaire instrument to capture the fundamental impact of Ramadan on strengthening social capital. In general, this study concludes that West Sumatra is superior to Yogyakarta for its social cohesion on 3 (three) indicators: moral feeling, sense of belonging, and social harmony. However, despite the difference in numbers between the two regions, there are differences among indicators. While for the other two indicators, safety feeling and tolerance, Yogyakarta is better than West Sumatra.